Mixed Hypertrophic and Dilated Phenotype of Cardiomyopathy in a Patient With Homozygous In-Frame Deletion in the MyBPC3 Gene Treated as Myocarditis for a Long Time - Blagova, Olga; Alieva, Indira; Kogan, Eugenia; Zaytsev, Alexander; Sedov, Vsevolod; Chernyavskiy, S.; Surikova, Yulia; Kotov, Ilya; Zaklyazminskaya, Elena V. (Frontiers in Pharmacology, 2020)
Hypertrophic cardiomyopathy (HCM) is the most common inherited disease, with a prevalence of 1:200 worldwide. The cause of HCM usually presents with an autosomal dominant mutation in the genes encoding one of more than 20 sarcomeric proteins, incomplete penetrance, and variable expressivity. HCM classically manifests as an unexplained thickness of the interventricular septum (IVS) and left ventricular (LV) walls, with or without the obstruction of the LV outflow tract (LVOT), and variable cardiac arrhythmias. Here, we present a rare case of mixed cardiomyopathy (cardiac hypertrophy and dilation) and erythrocytosis in a young patient. A 27-year-old man was admitted to the clinic due to biventricular heart failure (HF) NYHA class III. Personal medical records included a diagnosis of dilated cardiomyopathy (DCM) since the age of 4 years, and was, at the time, considered an outcome of myocarditis. Severe respiratory infection led to circulatory decompensation and acute femoral thrombosis. The combination of non-obstructive LV hypertrophy (LV walls up to 15 mm), LV dilatation, decreased contractility (LV EF 24%), and LV apical thrombosis were seen. Cardiac MRI showed a complex pattern of late gadolinium enhancement (LGE). Endomyocardial biopsy (EMB) revealed primary cardiomyopathy with intravascular coagulation and an inflammatory response. No viral genome was detected in the plasma or EMB samples. Whole exome sequencing (WES) revealed a homozygous in-frame deletion p.2711_2737del in the MyBPC3 gene. The clinically unaffected mother was a heterozygous carrier of this deletion, and the father was unavailable for clinical and genetic testing. Essential erythrocytosis remains unexplained. No significant improvement was achieved by conventional treatment, including prednisolone 40 mg therapy. ICD was implanted due to sustained VT and high risk of SCD. Orthotopic heart transplantation (HTx) was considered optimal. Early manifestation combined hypertrophic and dilated phenotype, and progression may reflect a complex genotype with more than one causative allele and/or a combination of genetic diseases in one patient.